2007
DOI: 10.1074/jbc.m608970200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent and -independent Binding of Soybean Calmodulin Isoforms to the Calmodulin Binding Domain of Tobacco MAPK Phosphatase-1

Abstract: The recent finding of an interaction between calmodulin (CaM) and the tobacco mitogen-activated protein kinase phosphatase-1 (NtMKP1) establishes an important connection between Ca 2؉ signaling and the MAPK cascade, two of the most important signaling pathways in plant cells. Here we have used different biophysical techniques, including fluorescence and NMR spectroscopy as well as microcalorimetry, to characterize the binding of soybean CaM isoforms, SCaM-1 and -4, to synthetic peptides derived from the CaM bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 68 publications
4
23
0
1
Order By: Relevance
“…10, b and c). This result agrees with the binding constant derived by ITC that is very similar to the previously reported binding constant of NtMKP1pA with the N-lobe fragment of SCaM isoforms (26). On the other hand, a few relatively small CSPs were observed for the C-lobe of SCaM4.…”
Section: Casupporting
confidence: 92%
See 2 more Smart Citations
“…10, b and c). This result agrees with the binding constant derived by ITC that is very similar to the previously reported binding constant of NtMKP1pA with the N-lobe fragment of SCaM isoforms (26). On the other hand, a few relatively small CSPs were observed for the C-lobe of SCaM4.…”
Section: Casupporting
confidence: 92%
“…6d). Because all the side chains of the Met residues in CaM (except for Met 76 in the central linker) form direct hydrophobic contacts with the CaMBDs in most Ca 2ϩ -CaM-target complexes, the methyl signals of the Met residue have been utilized extensively as a sensitive probe to monitor Ca 2ϩ -CaM-target interactions (26,27,47,48). For essentially all the methyl signals of SCaM4CT-Nt-MKP1, the corresponding signals are found in almost the same positions in the spectrum of the noncovalent SCaM4/ All experiments were performed at 30°C, 100 mM KCl, 2 mM CaCl 2 , 20 mM HEPES (pH 7.5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these titrations, the requirement for Ca 2ϩ as well as a portion of L-selectin predicted to be in the membrane-spanning region becomes apparent. The binding curve of LSELl with Ca 2ϩ -CaM is characterized by a two-step process, similar to that reported for other CaM-binding peptides (32,33). The first, which describes the binding of the first peptide to CaM, has a dissociation constant (K d ) on the order of 10 Ϫ9 M and is driven predominantly by entropic factors (Fig.…”
Section: Identification Of the L-selectin Cam Binding Site And Ca 2ϩsupporting
confidence: 74%
“…21 Using several biophysical techniques we recently characterized the interaction between CaM isoforms (mammalian CaM, soybean CaM isoforms SCaM-1 and SCaM-4) and a novel CaMBD derived from the Nicotiana tabacum mitogen-activated protein kinase phosphatase (NtMKP1). 22 The NtMKP1 protein was initially identified as a CaM-binding protein by Ohashi and coworkers, 23 and the same group recently showed that CaM-binding NtMKP1 homologs are also present in other plant species as well. 24 We found that each CaM isoform was capable of binding to the NtMKP1 CaMBD in the absence of Ca 2+ using only the apo-C-lobe, with the primary binding site consisting of NtMKP1 residues N438 -S449, and additional C-terminal residues G450 -K460 enhancing the overall binding affinity (K d ~10 -5 M).…”
mentioning
confidence: 99%